2012
DOI: 10.1016/j.cub.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Reward creates oculomotor salience

Abstract: Magazine R219of the population (which is now an evolutionary response). Wouldn't that be a good way of studying evolution in action over a few generations?One would think so. In particular, it is possible to measure all three components of the breeder's equation, and see directly whether R = h 2 S. But, quite often, it appears that R does not equal h 2 S. For example, a study on antler size in red deer showed that red deer with larger antlers had more offspring than red deer with smaller antlers, and antler si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
130
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 11 publications
20
130
4
1
Order By: Relevance
“…More specifically, we demonstrated that stimuli associated with primary reward can involuntary orient spatial attention and that this modulation critically depends on the properties of the primary reward. These results are consistent with recent experiments testing the incentive salience hypothesis in humans, and showing involuntary attentional interference effects by rewardassociated cue (Anderson et al, 2011a(Anderson et al, , 2011bHickey & van Zoest, 2012;Hickey et al, 2010aHickey et al, , 2010bHickey et al, , 2011. Critically, our results also revealed that this attentional capture is independent of the stimuli's low-level perceptual characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…More specifically, we demonstrated that stimuli associated with primary reward can involuntary orient spatial attention and that this modulation critically depends on the properties of the primary reward. These results are consistent with recent experiments testing the incentive salience hypothesis in humans, and showing involuntary attentional interference effects by rewardassociated cue (Anderson et al, 2011a(Anderson et al, , 2011bHickey & van Zoest, 2012;Hickey et al, 2010aHickey et al, , 2010bHickey et al, , 2011. Critically, our results also revealed that this attentional capture is independent of the stimuli's low-level perceptual characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that such attentional modulation is driven by initial orienting. This is congruent with eye tracking studies showing that reward-associated stimuli were more likely to draw initial gaze (Anderson & Yantis, 2012a;Hickey & van Zoest, 2012;Theeuwes & Belopolsky, 2012), but that the gaze is not maintained at this location for a longer period of time compared to neutral stimuli (Theeuwes & Belopolsky, 2012). This is consistent with the idea that involuntary attentional orienting toward cue-associated stimuli is an adaptive mechanism that allows the organism to rapidly orient its attentional resources toward the reward-related location, thereby increasing the possibility of obtaining rewards (Hickey et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, the observers were aware of the attribute of the target (e.g., the steep orientation) and the to-be-ignored distractor (e.g., the shallow orientation), making the top-down control ready to initiate the suppression mechanism. However, an initial attraction to the distractor with high reward salience followed by strong suppression could be an alternative mechanism for our findings, as indicated by a study using time-sensitive measures of eye movement (Hickey and van Zoest, 2012). Notably, the suppression of reward salience reduced its impairment on performance did not eliminate the physical salience effect on the search performance.…”
Section: Discussionmentioning
confidence: 56%
“…The ACC has been implicated in reward-mediated changes in attentional salience (Hickey and van Zoest, 2012) via an interaction with the MCL DA system (Berridge and Robinson, 1998). Enhanced ACC activation is associated with salient, attention-capturing events, even in the absence of competing stimuli.…”
Section: Discussionmentioning
confidence: 99%